2017
DOI: 10.1159/000464130
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal Cancer: New Insights into a Heterogenous Disease

Abstract: Background: Esophageal cancer represents a heterogeneous malignancy mostly diagnosed in advanced stages. Worldwide, squamous cell carcinomas (SCCs) continue to be the most prevalent subtype; however, in the Western countries, the incidence of adenocarcinomas is increasing and will exceed that of SCC in the near future. During the last decade, several landmark trials contributed to a better understanding of the disease and emphasized the importance of multimodal treatment protocols. Summary: With the introducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 56 publications
0
24
0
Order By: Relevance
“…Esophageal cancer (EC) is a highly aggressive tumor, and the majority of patients die of recurrent disease within 2 years from diagnosis; this happens even after a putative radical esophagectomy ( 1 , 2 ). EC presents two main histotypes, which occur in distinct esophageal districts: adenocarcinoma (EADC) and squamous cell carcinoma (ESCC).…”
Section: Introductionmentioning
confidence: 99%
“…Esophageal cancer (EC) is a highly aggressive tumor, and the majority of patients die of recurrent disease within 2 years from diagnosis; this happens even after a putative radical esophagectomy ( 1 , 2 ). EC presents two main histotypes, which occur in distinct esophageal districts: adenocarcinoma (EADC) and squamous cell carcinoma (ESCC).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies suggest that chemoradiation may lead to similar or greater outcomes than surgery alone, but results remain controversial [6]. trimodality approach has been shown, with the 2006 CALGB 9781 trial of 56 patients demonstrating an improvement of more than 50% in overall survival rates when compared with surgery alone [9]. Similarly, the CROSS study published in 2012 demonstrated signifi cantly increased survival with neoadjuvant chemoradiation compared with surgery alone (49.4 months vs. 24 months).…”
Section: Introductionmentioning
confidence: 99%
“…Esophageal cancer (EC) is one of the most common malignant tumors in the gastrointestinal tract . According to the WHO histological classification, EC mainly comprises squamous cell carcinoma (SCC) and esophageal adenocarcinoma, of which the proportion of SCCs is as high as 90% . In China, it is estimated that the average annual death total due to EC is ~150 thousand people, which accounts for 21.8% of all cancer mortalities .…”
Section: Introductionmentioning
confidence: 99%
“…1,2 According to the WHO histological classification, EC mainly comprises squamous cell carcinoma (SCC) and esophageal adenocarcinoma, of which the proportion of SCCs is as high as 90%. 3,4 In China, it is estimated that the average annual death total due to EC is~150 thousand people, which accounts for 21.8% of all cancer mortalities. 5 Among the leading causes of death, EC ranks fourth, with an average annual incidence of 17/1 000 000.…”
Section: Introductionmentioning
confidence: 99%